Audible empire : music, global politics, critique - Radano, Ronald Michael; Olaniyan, Tejumola (Refiguring American music., 2016)
Audible Empire's contributors rethink the mechanisms of empire, showing how musical practice has been important to its spread around the globe. The volume's fifteen interdisciplinary essays cover large swaths of genre, time, politics, and geography to put forth music as a means of comprehending empire as an audible formation.